Nontransient silk sandwich for soft, conformal bionic links. (January 2020) - Patil, Anoop C.; Bandla, Aishwarya; Liu, Yu-Hang; Luo, Baiwen; Thakor, Nitish V.
Graphical abstract: Highlights: Soft flexible bionic links on nontransient hydrated silk fibroin films are reported. Silk links conform to the challenging wet slimy surfaces of the biological milieu. First of its kind development of silk links for the peripheral nerves and the cortex. Silk links validated through neural recording experiments in an anesthetized rodent model. Silk bionic links can enable nontransient silk bioelectronics for in vivo use. Abstract: Soft biointerfaces that maintain intimate contact with the smooth but curved tissue and organ surfaces are critical for providing reliable readouts of in vivo electrical activity. In contrast to conventional biodegradable class of silk scaffolds, we report for the first time, nontransient, or sustainable and implantable silk fibroin bionic interfaces for direct electrical recording of a variety of biopotentials such as neural activity from the peripheral nerves and the cortex. This new class of soft and flexible interfaces are enabled by a silk fibroin-based strategy that relies on substrates and superstrates of nontransient water-stable silk for supporting the electrode constructs. We present SILK-SEAL that involves soft assembly of thin silk layers resulting in a silk sandwich, and QUICK-SILK, an elastomer-silk bandage backing enabling fully functional silk electrode sensors that can be securely deployed in vivo . The resulting novel thin film devices achieve biopotential recording from the peripheral nerve and the cortex in a rodent model, thanks to the thin form factor of the silk film appliqués that enable conformal lamination on the target tissue surfaces, and the adhesive elastomer-silk backing, a suture-free approach that assists in pasting and securing the arrays in place. The neural recording experiments demonstrate a novel mode of use for the silk sensors as non-dissolvable biointerfaces, providing evidence for their application in preclinical research studies. The silk interfaces reported here, serve as the first significant leap towards non-dissolvable silk bioelectronics for in vivo use.